A surveillance study of patterns of reirradiation practice using external beam radiotherapy in Japan. (21st December 2020) - Yamazaki, Hideya; Suzuki, Gen; Aibe, Norihiro; Nakamura, Satoaki; Yoshida, Ken; Oh, Ryoongjin; ,
Abstract: The aim of this study was to survey the present status and patterns of reirradiation (Re-RT) practice using external beam radiotherapy in Japan. We distributed an e-mail questionnaire to the Japanese Society for Radiation Oncology partner institutions, which consisted of part 1 (number of Re-RT cases in 2008–2012 and 2013–2018) and part 2 (indications and treatment planning for Re-RT and eight case scenarios). Of the 85 institutions that replied to part 1, 75 (88%) performed Re-RTs. However, 59 of these 75 institutions (79%) reported difficulty in obtaining Re-RT case information from their databases. The responses from 37 institutions included the number of Re-RT cases, which totaled 508 in the period from 2009 to 2013 (institution median 3; 0–235), and an increase to 762 cases in the period from 2014 to 2018 (12.5; 0–295). A total of 47 physicians responded to part 2 of the survey. Important indications for Re-RT that were considered were age, performance status, life expectancy, absence of distant metastases and time interval since previous radiotherapy. In addition to clinical decision-making factors, previous total radiation dose, volume of irradiated tissue and the biologically equivalent dose were considered during Re-RT planning. From the eight site-specific scenarios presented to the respondents, >60% of radiation oncologists agreed to perform Re-RT. Re-RT cases have increased in number, and interest in Re-RT among radiation oncologists has increased recently due to advances in technology. However, several problems exist that emphasize the need for consensus building and the establishment of guidelines for practice and prospective evaluation.